2022
DOI: 10.1002/pld3.396
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis gene co‐expression network

Abstract: Identifying genes that interact to confer a biological function to an organism is one of the main goals of functional genomics. High‐throughput technologies for assessment and quantification of genome‐wide gene expression patterns have enabled systems‐level analyses to infer pathways or networks of genes involved in different functions under many different conditions. Here, we leveraged the publicly available, information‐rich RNA‐Seq datasets of the model plant Arabidopsis thaliana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 121 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…The gene losses avoid essential genes while simplifying GRNs. When mapping the mangrove gene losses to Arabidopsis thaliana , we found that 2,624 of the 10,480 loss events could be assigned to the reliably connected gene network that contains 6,411 of the 27,416 total genes ( Burks et al 2022 ; Fisher’s exact test; P = 2.1 × 10 −7 ). The gene losses are also enriched on large gene families.…”
Section: Resultsmentioning
confidence: 99%
“…The gene losses avoid essential genes while simplifying GRNs. When mapping the mangrove gene losses to Arabidopsis thaliana , we found that 2,624 of the 10,480 loss events could be assigned to the reliably connected gene network that contains 6,411 of the 27,416 total genes ( Burks et al 2022 ; Fisher’s exact test; P = 2.1 × 10 −7 ). The gene losses are also enriched on large gene families.…”
Section: Resultsmentioning
confidence: 99%
“…Such regulatory networks are likely to be highly interconnected, and thus small-effect alleles across a wide range of loci, even those seemingly unrelated to the trait under study, may in fact have an impact on a trait such as shoot branching [ 75 ]. It will be interesting to investigate the overlap between our candidate QTL and their positioning in such regulatory networks, for example by exploring existing large-scale transcriptome networks [ 76 ] or by exploring co-expression patterns more specifically across a range of mutants in “core” shoot branching regulators (such as MAX , SMAXL and BRC genes) [ 24 , 77 ]. Furthermore, given the difference between LN and HN populations we observe, it may be fruitful to explore the transcriptomic changes in young buds from plastic and non-plastic genotypes growing under different nitrate conditions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…One approach could be to assess their expression during resistance or use gene co-expression networks for understanding their role in resistance (see, for example, refs. [34,35] for such an approach that was used to characterize stress responsive genes). Novel resistance genes prioritized using computational approaches could be the candidates for experimental verification using wet lab assays, which may also provide insights into yet unknown mechanisms of resistance.…”
Section: Discussionmentioning
confidence: 99%